곡기생(槲寄生)의 파골세포 분화 및 골흡수 억제기전 연구 - 손동빈; Dongbin Son; 이수민; Sumin Lee; 박서연; Seoyeon Park; 이현준; Hyunjun Lee; 정혁상; Hyuk-sang Jung; 김은영; Eun-young Kim; et al. (大韓本草學會誌, 2025)
Objectives : Osteoporosis is a condition characterized by a decrease in bone mass, leading to an increased risk of bone abnormalities, impacting both an individual's health and socioeconomic aspects. This disease is known to be caused by excessive osteoclast activity. Through efficacy and existing research, it is inferred that Viscum album L. var. coloratum Ohwi (VL) is expected to inhibit the differentiation of osteoclasts and bone resorption mechanisms. This study investigates the potential of VL in suppressing osteoclast differentiation and bone resorption. Methods : RAW 264.7 cells were treated with RANKL to differentiate into osteoclasts, and the inhibitory effects of water VL extract (WVL) and ethanol VL extract (EtVL) on osteoclast differentiation were compared using the TRAP staining kit. The number of TRAP-positive cells and TRAP activity were measured. Protein and mRNA expression of NFATc1 and c-Fos were quantified. The mRNA expression of differentiation, bone resorption and osteoclast fusion factors in osteoclasts was also assessed. Results : The EtVL treatment reduced the number of TRAP positive cells and TRAP activity. The protein and mRNA expression of NFATc1 and c-Fos decreased. The mRNA expression of born resoption factors, MMP-9 and CA2, was inhibited. Additionally, the mRNA expression of osteoclast differentiation factor TRAP, osteoclast fusion factor ATP6v0d2 and OSCAR, also decreased. Conclusions : These results suggest that EtVL may be utilized for the treatment of osteoporosis by inhibiting osteoclast differentiation, bone resorption and osteoclast fusion factors.